2019
DOI: 10.1016/j.enpol.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The drivers of energy-related financial hardship in Australia – understanding the role of income, consumption and housing

Abstract: The drivers of energy-related financial hardship in Australiaunderstanding the role of income, consumption and housing Saunders and Bedford (2017) demonstrated that income levels are inadequate for some Australian households to maintain a basic standard of living. Analysing utility bills can extend this consideration of income adequacy issues given the essential nature of services such as electricity, telephony and water. This article builds on the work presented by Simshauser and Nelson (2014) about key demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Australian households that were disconnected or at risk of disconnection experienced very difficult financial circumstances, in which they often struggled to afford necessities such as food and housing [59]. In a recent article, Nelson et al (2019) suggested, among other solutions, increasing income support for particular groups (including those on Newstart) as well as the reform of state-based energy concessions to combat energy poverty [60].…”
Section: Discussionmentioning
confidence: 99%
“…Australian households that were disconnected or at risk of disconnection experienced very difficult financial circumstances, in which they often struggled to afford necessities such as food and housing [59]. In a recent article, Nelson et al (2019) suggested, among other solutions, increasing income support for particular groups (including those on Newstart) as well as the reform of state-based energy concessions to combat energy poverty [60].…”
Section: Discussionmentioning
confidence: 99%
“…Nelson et al . () identified household size as being related to energy‐related financial hardship. KPMG () also noted that large low‐income families with five or more people would be most affected by rising energy costs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, iIncreasing financial social assistance may reduce severe effects associated with food insecurity in households. For example, in Newfoundland and Labrador in Canada, food insecurity dropped significantly in 2007-2011 because of social assistance reforms (Nelson et al 2019). It has been shown that a one-off increase in social assistance benefits leads to a significant decrease in moderate and severe food insecurity (Li et al 2016).…”
Section: Discussionmentioning
confidence: 99%